Continuous Meniscal Repair Technique Allows for Shorter Operative Time and Learning Curve Compared With Traditional Vertical Mattress Technique in Controlled Arthroscopic Training in Porcine Model - José Leonardo Rocha de Faria, M.D., M.Sc. Ph.D; João Vieira de Almeida Neto, M.D; Bruno Couto Gonçalves, M.D; Douglas Mello Pavão, M.D., M.Sc. Ph.D; João Antonio Matheus Guimarães, M.D., Ph.D; Valdeci Manoel de Oliveira, M.D., Ph.D; Robert F. LaPrade, M.D., Ph.D; Djalma Rabelo Ricardo, Ph.D; Rodrigo Salim, M.D., Ph.D (Elsevier, 2024)
Purpose: To compare the amount of time used to perform meniscal suturing on a standardized lesion using either a traditional or continuous arthroscopic suturing technique. Methods: A preclinical study was carried out with 21 medical doctors who underwent training in the 2 modalities of meniscal repair by arthroscopy in an animal model laboratory. Participants performed both types of sutures with a previously standardized lesion. The execution time of the techniques was measured, and an experienced surgeon evaluated the stability of a meniscal tear after the repair. Data were analyzed using a t test for paired samples to calculate the difference between the execution times of the techniques. Results: The time required to perform the continuous meniscal suture was shorter than that of the traditional suture. After statistical analysis, the time difference between the techniques was significant (mean difference 4:17 ± 5:30 minutes; 95% confidence interval, 1:46-6:46 minutes). Surgeons took less time than residents for the traditional suture (P = .036), but the times were similar for the continuous suture. This suggests that experience level has a greater effect on the time needed for the traditional suture than for the continuous suture. Conclusions: The continuous suture technique was performed in a shorter time compared with the traditional suture technique in a porcine model. Clinical Relevance: The results of this preclinical study suggest that the continuous vertical inside-out meniscal suture technique can enhance surgical procedures for longitudinal tears requiring ≥4 stitches, offering a faster and more intuitive learning curve compared with the traditional inside-out suture technique.